Oční komplikace periferní parézy nervus facialis a možnosti jejich terapeutického řešení - Klímová, Aneta; Bydžovský, Jan; Skalická, Pavlína (Neurologie pro praxi, 2023)
Peripheral lesion of the facial nerve leads to ipsilateral palsy of facial muscles. Weakening of the orbicularis oculi muscle results in inability to close the eyelids, i.e., lagophtalmos. As a result of lagophtalmos, the lower parts of the eye surface dry and cause a formation of exposure keratopathy of variable severity. Chronic corneal changes lead to development of vascularized corneal scar, which permanently deteriorates the visual acuity. Immediately after the diagnosis of peripheral facial nerve palsy by the neurologist, frequent application of ophthalmic lubricants and an early ophthalmological examination are recommended. The treatment of eye complications depends on the character of corneal involvement and extent of lagophtalmos, considering the possibility of its spontaneous restitution. The therapy is surgical in serious cases, aimed at adjusting the position of the eyelids, and in case of a non-healing corneal ulcer, the amniotic membrane transplant is indicated.
Keywords: Eye Manifestations; nervus facialis; oftalmologické chirurgické výkony; Ophthalmologic Surgical Procedures; Facial Nerve; oční symptomy; Amnion; Blepharoplasty; výsledek terapie; Middle Aged; Bellova paréza; Neuroma, Acoustic; ženské pohlaví; Anastomosis, Surgical; Humans; lagoftalmus; amnion; Bell Palsy; anastomóza chirurgická; vestibulární schwannom; blefaroplastika; lidé středního věku; Female; Treatment Outcome; Lagophthalmos; lidé